PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PD. KOPI KUDA BANDAR LAMPUNG - Andy Fitriyadi Dharmat Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
Consumer perception of the same product or brand does not necessarily produce the samerating because not all consumers have complete knowledge of the condition of the product. Therefore,to be able to provide superior value to consumers and be able to calm competition, the company mustknow the consumer's judgment or perception of the competitor's product or brand, so that consumerpreferences can be known for prices based on consumer perception.In this research the consumer's decision to buy a product is based on the price. So from thatprice has a strong factor on the purchasing decision of a product. Related to this problem, it isnecessary to study the variables that influence it so that efforts can be made to solve the problem of thelow market share of coffee products from the PD Kopi Kuda. Then the research topic taken byresearchers is: